Causes of death among persons diagnosed with hepatitis C infection in the pre‐ and post‐DAA era in England: A record linkage study. Issue 7 (23rd April 2019) - Simmons, Ruth; Ireland, Georgina; Ijaz, Samreen; Ramsay, Mary; Mandal, Sema; ,
Summary: Through record linkage, we describe the causes of death among persons with diagnosis of hepatitis C virus (HCV) in England. Persons ≥1 year with anti‐HCV/HCV‐PCR tests reported to PHE sentinel surveillance during 2002‐2016 were linked to death registrations from the Office for National Statistics during 2008‐2016. We found that 8.6% of the 204 265 with evidence of HCV during the study period died. Among them, external causes (accidental poisoning from drugs) and liver disease (end‐stage liver disease, liver cancer, hepatitis, alcohol‐ and non–alcohol‐related) were the leading underlying causes of death (18% and 34.5%, respectively); the latter increased to 49.2% if reported anywhere on the death certificate. Median age of death was lower in persons with evidence of HCV than the general population (53 years vs 81 years). A higher proportion of persons with HCV died of external causes, liver disease and HIV compared to the general population ( P < 0.001). Potential impact of new HCV treatments was observed as a relative reduction in liver‐related deaths in 2016 compared with 2015. Recording of HCV as a contributory cause of death was 28.4% for all underlying causes, but 58.8% among the subgroup who died of liver disease. Data linkage between laboratory diagnosis and deaths data is an important tool for monitoring all‐cause mortality among those with HCV and quantifying under‐reporting of HCV in death registrations. Changes in mortality trends (causes and prematurity) in people with HCV can help evaluate the impact in the UK of HCV treatment scale‐up and other interventions to achieve HCV elimination.